Interação salinidade e nitrogênio sobre os componentes nutricionais e de produção do capim tanzânia - Maia, Priscila de Melo Evangelista (Universidade Federal Rural do Semi-Árido, 2014)
The arid and semiarid regions have suffered from the problem of water scarcity, rising steadily through periods of drought. In northeastern Brazil, to meet the water needs is common to drill wells, however, due to geological formation of its aquifers, most of these wells has brackish waters. Agriculture and livestock are important activities in these regions and is responsible for much of the water consumption; an alternative to increase the availability of water for agricultural activities would be to use water from shallow wells for irrigation of halophytes or crops tolerant to salinity. Forage crops are considered tolerant plants, mineral nutrition being a very important factor for the production losses is minimal, and, according to several authors nitrogen, can be a reducer of the effects caused by salt stress, and promote the growth of plant. Aiming to evaluate the interactive effect of salinity levels and nitrogen fertilization on yield and chemical composition of Tanzania grass developed this work in a greenhouse in pots , the treatments consisted of five levels of salinity ( S1 = 0 5 dS m -1 , S2 - 1.5 dS m -1 , S3 - 3.0 dS m -1 , S4 - 4.5 dS m -1 and S5 - 6.0 dS m -1 ) and four nitrogen ( N1 = 0, N2 = 0.8, N3 = N4 = 1.6 and 2.3 g pot-1 ) . Evaluated the production components leaf area (LA), fresh weight and dry weight of leaves ( MFF ) and ( MSF ) , crude protein , and macronutrient content of Cl- and Na+ . There was a significant effect for the interaction of salinity and N levels for all components of the production so that as was the high level of salinity production was reduced, even though the level of salinity S3 N rates possible a lower reduction ratio. Generally observed increase in the concentration of nutrients and PB with increasing salinity of irrigation probably due to the concentration effect of these nutrients in the plant since the dry weight was inversely proportional. It was also found that irrigation with high salt inhibited the beneficial effect of nitrogen on the growth of grass Tanzania
Cultivation Tanzania grass under salt stress and nitrogen levels
Keywords: Water scarcity; Salinity; Nitrogen; Panicum maximum jacq; Irrigação; Adubação nitrogenada; Estresse salino; Panicum maximun; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM